Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1665/034.021.0202
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Observations on the Gonads and Neurosecretory Cells ofSchistocerca gregariaAfter Treatment with Lufenuron (CGA-184699)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Thus, the results of this study indicate that buprofezin and the pyriproxyfen are involved in dismantling germ cells and the connective tissue component of both external and internal sheaths. These results are similar to those of Ghazawy (2012), who also reported correlations between the action of the chitin biosynthesis inhibitor lufenuron and the ultrastructure and formation of testicular cysts of S. gregaria.…”
Section: Testis Analysessupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the results of this study indicate that buprofezin and the pyriproxyfen are involved in dismantling germ cells and the connective tissue component of both external and internal sheaths. These results are similar to those of Ghazawy (2012), who also reported correlations between the action of the chitin biosynthesis inhibitor lufenuron and the ultrastructure and formation of testicular cysts of S. gregaria.…”
Section: Testis Analysessupporting
confidence: 90%
“…Reports of products that inhibit chitin biosynthesis and that are involved in the losses of reproductive potential and development of insect ovaries and testes exist (CHANGMANN et al, 2008;GHAZAWY, 2012).…”
Section: Studies In Whitefly (Trialeurodes Vaporariorummentioning
confidence: 99%
See 1 more Smart Citation
“…They also saw that nymphs treated with the insect growth regulator cascade showed a notable decrease in the number of cerebral NC as well as the number of neurosecretory particles carried by the axoplasm. Ghazawy [40] also found that treatment of fifth-instar Schistocerca gregaria with lufernuron, a chitin synthesis inhibitor, reduced the release of neurosecretory material from the brain NC in the pars intracerebral.…”
Section: Discussionmentioning
confidence: 94%
“…Tests with lufenuron presented a sperm reduction in males of Anthonomus grandis Boheman (1843) (Coleoptera: Curculionidae), the boll weevil, as well as ovarian changes in females (Costa, et al, 2017). The same compound was tested in S. gregaria, showing analyzes of ovarian and testicular disruption (Ghazawy, 2012). Tail et al (2008) observed, in diflubenzuron treatment of S. gregaria, a reduction in eggs number per ootheca and, with the observed results, formulated a hypothesis about the treatment have reduced the ecdysteroids levels in hemolymph, reflecting in ovarian synthesis reduction due to alterations in follicular chambers.…”
Section: Potential In Reproductive Modificationsmentioning
confidence: 87%